WORLD LEADERS DURING COVID-19 - Hustad, Douglas; Lurie, Mark N. (Minneapolis, Minnesota : Abdo Publishing, 2021)
In late 2019, health officials noticed a new disease spreading in Wuhan, China. They named it COVID-19. Within a few months, it became a pandemic that dramatically changed life for nearly everyone on Earth. Millions of people became sick, and hundreds of thousands died. Leaders ordered whole states and countries to stay home to slow the disease's spread. Companies closed or went out of business. Meanwhile, health-care workers on the front lines saved lives and raced to find treatments. In the Core Library Guide to COVID-19, readers will learn about the disease, how it spread across the globe, and the ways it has changed society. As the COVID-19 pandemic unfolded, political leaders and health officials worked to understand the disease, slow the infection rate, and lower the death toll. World Leaders during COVID-19 examines how different leaders reacted, how the messages to their citizens were received, and how effective their measures proved to be.
Includes bibliographical references and index.
Keywords: COVID-19 (Disease) -- Juvenile literature; Coronavirus infections -- Juvenile literature; Communicable diseases -- Prevention -- Juvenile literature; Statesmen -- Juvenile literature